ACTIVE SURVEILLANCE FOR ASYMPTOMATIC COLONIZATION WITH MULTIDRUG RESISTANT GRAM-NEGATIVE BACILLI IN PRE-OPERATIVE PAEDIATRIC CONGENITAL CARDIAC DISEASE PATIENTS; PRELIMINARY RESULTS - Zaidi, Sabeen Khurshid; Khalil, Hafsa; Ahmed, Iftikhar; Akbar, Hajira; Saleem, Kamal; Ali, Waqar (Pakistan Armed Forces Medical Journal, 2015)
Objective: To carry out active surveillance for Gram negative Multi drug resistant Bacilli in pre-operative congenital heart disease patients.Study Design: Prospective cohort study.Place and Duration of Study: This study was conducted at Department of Paediatric Cardiac Surgery AFICNIHD, Rawalpindi from 1st Jan 2015 to 28th Feb 2015.Methodology: It is an ongoing study, but a preliminary analysis has been conducted on a sample size of 50 patients. Informed consent was taken from patient’s parents before sample collection. Samples included throat and rectal swabs which were processed for culture and antibiotic sensitivity of gram negative bacilli isolated.Results: A total of 14 (28%) patients were identified who were colonized with Multi drug resistant gram negative bacteria (MDR-GNB). Nine isolates were ESBL producers. None of the strains showed Carbapenem resistance. Isolated MDR-GNB were Escherichia coli (n=10), Proteus species (n=01), Acinetobacter species (n=1) and Klebsiella pneumoniae (n=02).Conclusion: The presence of MDR GNB in preoperative paediatric patients addresses the need for antibiotic stewardship programmes and judicious use of antimicrobials in community based settings.